Work design improvement at Miroad Rubber Industries Sdn. Bhd. - Ng, Si Jin; Samsuni, Muhamad Husni; Chen, Xue Chee; Tay, Poh Jing; Lee, Kah Ching; Mahmood, Salwa; Tajurahim, Nurul Ainina Nadhirah; Ngadiman, Nor Hasrul Akhmal (Penerbit UTHM, 2020)
Erul Food Industries known as Salaiport Industry is a family-owned company and was established on July 2017. Salaiport Industry apparently moved to a new place at Pedas, Negeri Sembilan. Previously, Salaiport Industry operated in-house located at Pagoh, Johor. This small company major business is producing frozen smoked beef, smoked quail, smoke catfish and smoked duck. The main frozen product is smoked beef. The frozen smoked meat produced by Salaiport Industry is depending on customer demands. Usually the company produce 40 kg to 60 kg a day and operated between for four days until five days. Therefore, the company produce approximately around 80 kg to 120 kg per week. The company usually take 2 days for 1 complete cycle for the production as the first day the company will only receive the meat from the supplier and freeze the meat for use of tomorrow.